2019
DOI: 10.1029/2018wr024428
|View full text |Cite
|
Sign up to set email alerts
|

Physical Controls on Salmon Redd Site Selection in Restored Reaches of a Regulated, Gravel‐Bed River

Abstract: Large‐scale river restoration programs have emerged recently as a tool for improving spawning habitat for native salmonids in highly altered river ecosystems. Few studies have quantified the extent to which restored habitat is utilized by salmonids, which habitat features influence redd site selection, or the persistence of restored habitat over time. We investigated fall‐run Chinook salmon spawning site utilization and measured and modeled corresponding habitat characteristics in two restored reaches: a reach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 110 publications
2
10
0
Order By: Relevance
“…The longer life span of the studied gravel augmentations in Norway can be explained by the relatively stable morphodynamics due to semi-and non-fluvial geomorphology and low suspended load . According to Harrison et al (2019), the spawning gravel augmentation measure with the longest life span documented so far, was a 14-yearold project for Chinook in Merced River, California. The documented life span of the measure in Matreelva exceeds this period (18 years).…”
Section: Egg Survival and Juvenile Fish Densitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The longer life span of the studied gravel augmentations in Norway can be explained by the relatively stable morphodynamics due to semi-and non-fluvial geomorphology and low suspended load . According to Harrison et al (2019), the spawning gravel augmentation measure with the longest life span documented so far, was a 14-yearold project for Chinook in Merced River, California. The documented life span of the measure in Matreelva exceeds this period (18 years).…”
Section: Egg Survival and Juvenile Fish Densitiesmentioning
confidence: 99%
“…Augmentations therefore have a limited life span depending on fine sediment load (Pulg et al, 2013), flood frequency, and magnitude (Merz et al, 2006). Strategies for resupplying gravel are not well developed because case studies on the effects of such gravel augmentations are usually limited to short periods of 1 to 5 years, if conducted at all, or ignore sediment monitoring (Sear & DeVries, 2008a;Pedersen et al, 2009;Harrison et al, 2019). In a study on restored spawning sites in the USA, Chinook salmon (Oncorhynchus tshawytscha, Walbaum 1792) used the sites for spawning after 14 years, which to our knowledge is the only study that evaluates spawning habitats for longer than 10 years (Harrison et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, coordinated efforts by agencies collecting data that improve accessibility and transparency can contribute to a wealth of data with which to address a wide range of questions. These data repositories can provide the information necessary to parameterize relationships that can facilitate extrapolation across scales (McHugh et al, 2017) and assess management or restoration over time (Harrison et al, 2019).…”
Section: Best Practicesmentioning
confidence: 99%
“…For example, in the gravel-cobble bedded reaches of California's Merced River below Crocker-Huffman Dam there have been over 6 km of river channel and off-channel habitats restored for fall-run Chinook salmon (Oncorhynchus tshawytscha) using the concept of rescaling the river channel to remediate impacts from flow regulation and gravel and sand mining (Figure 2). While it has been demonstrated that rescaling river channels below dams can improve salmonid habitat [38,39], few studies have discussed how to design these features within the template of regulated and highly modified river corridors. An example habitat restoration project using rescaling on the Merced River California for fall-run Chinook salmon.…”
Section: Introductionmentioning
confidence: 99%